High-Intensity Interval Training Improves Markers of Oxidative Metabolism in Skeletal Muscle of Individuals With Obesity and Insulin Resistance - Matos, Mariana Aguiar de; Vieira, Dênia Vargas; Pinhal, Kaio Cesar; Lopes, Jennifer Freitas; Dias-Peixoto, Marco Fabrício; Pauli, José Rodrigo; Castro Magalhães, Flávio de; Little, Jonathan P.; Rocha-Vieira, Etel; Amorim, Fabiano Trigueiro (Frontiers in Physiology, 2018)
Background: The excess body fat characteristic of obesity is related to various metabolic alterations, which includes insulin resistance (IR). Among the non-pharmacological measures used to improve insulin sensitivity are aerobic physical training, such as high-intensity interval training (HIIT). This study investigated the effects of 8 weeks of HIIT on blood and skeletal muscle markers related to IR and oxidative metabolism in physically inactive individuals with obesity and compared the changes between insulin resistant and non-insulin resistant phenotypes. Methods: Initially to investigate the effect of obesity and IR in the analyzed parameters, insulin-sensitive eutrophic volunteers (CON; n = 9) and obese non-insulin (OB; n = 9) and insulin-resistant (OBR; n = 8) were enrolled. Volunteers with obesity completed 8 weeks of HIIT in a cycle ergometer. Venous blood and vastus lateralis muscle samples were obtained before and after the HIIT. Body composition and peak oxygen consumption (VO2peak) were estimated before and after HIIT. Results: HIIT reduced IR assessed by the homeostatic model assessment of insulin resistance (HOMA-IR) in OBR (4.4 ± 1.4 versus 4.1 ± 2.2 μU L−2), but not in OB (HOMA-IR 1.8 ± 0.5 versus 2.3 ± 1.0 μU L−2) volunteers. HIIT increased VO2peak with no change in body fat in both groups. In skeletal muscle, HIIT increased the phosphorylation of IRS (Tyr612), Akt (Ser473), and increased protein content of β-HAD and COX-IV in both groups. There was a reduction in ERK1/2 phosphorylation in OBR after HIIT. Conclusion: Eight weeks of HIIT increased the content of proteins related to oxidative metabolism in skeletal muscle of individuals with obesity, independent of changes total body fat.